O Estudo de Probabilidade no Ensino Médio - Carloni, Paula Carolina (2019)
The purpose of this paper is to show the student the importance of probability in everyday life. Firstly, a survey was made of students' prior knowledge of probability. Next, the historical aspects of probability and geometric probability were discussed. The next step was to construct the concepts and definitions of probability, analyzed several problems were, whose solutions were constructed with the intervention of the teacher, inducing the students to think and rethink these basic concepts. Then, a didactic sequence was applied on the subject probability, with the perspective of producing meaningful and contextualized learning. Finally, a written evaluation was applied on the topics addressed in the work.